The Supernatural in the Tragedies of Shakespeare and Webster - Shanker, Kutty Sevithri (My University, 1962)
A brief survey of the treatment of the supernatural in Elizabethan drama before Shakespeare, the popular beliefs about ghosts. witches and demoniacal possession. and an examination of the tragedies of Shakespeare and Webster in which the supernatural figures prominently.
[missing pages 42 and 43]
Keywords: English; English Language and Literature